Characterizing intramuscular connective tissue degradation by matrix metalloproteinase - 9 in extended aging of beef - Alves Koulicoff, Larissa (Kansas State University, 2022)
Tenderness is negatively affected by intramuscular connective tissue (IMCT), which provides a "background toughness" in meat. In order to better utilize “lower quality” beef cuts, which contain a high amount of IMCT, meat scientists need to better understand connective tissue and come up with strategies to mitigate the effect of connective tissue on beef tenderness. A mechanism for increasing IMCT tenderness could be attributed to the activity of matrix metalloproteinases (MMPs), which is known for remodeling connective tissue components in the live animal. Hence, this research aims to characterize structural and property modifications of IMCT during extended aging and how MMPs participate in this process. For conducting the experiments, Longissimus lumborum (LL), Gluteus medius (GM), and Gastrocnemius (GT) were collected from 10 USDA choice carcasses, fabricated and assigned to one of four aging periods: 3, 21, 42, or 63 days (n = 120). In chapter 2, tenderness of meat and structural modifications of the connective tissue were explored. Warner-Bratzler shear force decreased, and connective tissue texture softened after 21 days of postmortem aging (P < 0.05). Transition temperature of collagen decreased (P < 0.01) after 42 days of postmortem aging. Trained panelists identified steaks aged for only 3 days were with lower myofibrillar tenderness (P < 0.05), more connective tissue amount (P < 0.05) and less tender for overall tenderness (P < 0.01) compared to steaks from the other aging periods. Collagen content did not change throughout the aging periods (P > 0.10). However, collagen structure was altered where relative % of γ chain that decreased after 42 days of postmortem aging (P < 0.05), while α1 chain % increased at 63 days (P < 0.01). Finally, the LL and GT had a decrease in the 75 kDa aggrecan fragments from 3 to 21 to 42 days (P < 0.05). In chapter 3, the effect of MMPs were explored in the extended aging utilizing the collagen zymography technique. MMP-9 was shown to be the active collagenase during aging of meat, and the highest activity was detected at 3 days of postmortem aging (P < 0.05). Moreover, when testing MMP-9 in refrigerated temperatures at 4 °C, activity was not detected prior to 42 days of storage in the cooler, where the activity was higher for the 63 than 42 days of aging (P < 0.05). In order to improve activity, different zinc concentrations were tested in MMP-9, and supplementation with 20 µM of ZnCl2 showed the highest MMP-9 activity when compared to other levels of supplementation (P < 0.01). The findings from this research filled a knowledge gap on the IMCT structural modification during postmortem aging in beef. Lastly, we provided concrete proof that MMP-9 activity can be stimulated with low concentration of zinc in combination. Further research still needs to be done to better understand MMP-9 mechanism during postmortem aging of meat. With a better understanding of MMP-9 in the aging process, the beef industry can provide better connective tissue management strategies for lower quality beef cuts.
Keywords: Collagen; Aggrecan; Zymography; Matrix metalloproteinase - 9; Beef; Meat